2011
DOI: 10.3109/00207454.2011.568656
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Emotional Modulation of Motor Response Time Despite Psychomotor Slowing in Young-Old Adults

Abstract: Whereas aging affects cognitive and psychomotor processes negatively, the impact of aging on emotional processing is less clear. Using an "old-new" binary decision task, we ascertained the modulation of response latencies after presentation of neutral and emotional pictures in "young" (M = 27.1 years) and "young-old" adults with a mean age below 60 (M = 57.7 years). Stimuli varied on valence (pleasant, neutral, and unpleasant) and arousal (high and low) dimensions. Young-old adults had significantly longer rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…We showed that age was associated with decreased amygdala somatomotor cortical rsFC, in accord with studies reporting age-related changes in emotional motor activities. For instance, pleasant compared to unpleasant visual stimulation facilitated motor response in young but not older adults ( Vernazza-Martin et al, 2017 ; see Hälbig et al, 2011 for contrasting findings). Aging was associated with decreased response to emotionally arousing stimuli in the occipital and temporal visual cortices, inferior parietal cortex, and supplementary motor area ( Kehoe et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…We showed that age was associated with decreased amygdala somatomotor cortical rsFC, in accord with studies reporting age-related changes in emotional motor activities. For instance, pleasant compared to unpleasant visual stimulation facilitated motor response in young but not older adults ( Vernazza-Martin et al, 2017 ; see Hälbig et al, 2011 for contrasting findings). Aging was associated with decreased response to emotionally arousing stimuli in the occipital and temporal visual cortices, inferior parietal cortex, and supplementary motor area ( Kehoe et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%